1997
DOI: 10.1246/cl.1997.499
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thiophene 1-Oxides Kinetically Stabilized by Bulky Substituents at the 3- and 4-Positions

Abstract: Oxidation of 3,4-di-t-butyl- and 3,4-di-1-adamantyl-, and 2,4-di-t-butylthiophenes with an equimolar amount of m-chloroperbenzoic acid in the presence of BF3•Et2O gave the corresponding thiophene 1-oxides in good yields, which are stable enough to be isolated in pure crystalline form. An X-ray single crystal structure analysis led to the conclusion that thiophene 1-oxides would not be aromatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…These considerations prompted us to develop an alternative synthesis of S-iminated thiophenes. Previously, we reported that the oxidation of 6a with mchloroperbenzoic acid (MCPBA) in the presence of BF 3 • Et 2 O affords the corresponding thiophene 1-oxide (1a) in good yield [14]. We therefore examined the conversion of 1a to 3b and the related sulfilimines [15].…”
Section: Preparation Of Sulfilimine Derivatives From 34-mentioning
confidence: 99%
“…These considerations prompted us to develop an alternative synthesis of S-iminated thiophenes. Previously, we reported that the oxidation of 6a with mchloroperbenzoic acid (MCPBA) in the presence of BF 3 • Et 2 O affords the corresponding thiophene 1-oxide (1a) in good yield [14]. We therefore examined the conversion of 1a to 3b and the related sulfilimines [15].…”
Section: Preparation Of Sulfilimine Derivatives From 34-mentioning
confidence: 99%
“…The crude oil was then purified by flash chromatography (silica gel 4:1 = Hex/EtOAc) to yield methyl 5-oxo-1-(2-oxo-2-phenylethyl)cyclohex-3-enecarboxylate as a white solid (0.98 g, 3.6 mmol, 52%), mp 112−114°C. 5-Oxo-1-(2-oxo-2-phenylethyl)cyclohex-3-ene carboxylic acid (12). To a chilled solution (0°C) solution of methyl 5-oxo-1-(2-oxo-2-phenylethyl)cyclohex-3-enecarboxylate (1.20 g, 4.41 mmol, 1 equiv) in THF (60 mL) was added a solution of lithium hydroxide (116 mg, 4.85 mmol, 1.1 equiv) in H 2 O (60 mL), and the resulting solution was stirred for 1 h, warmed to rt, and stirred for an additional 2 h then quenched with 1 N HCl (10 mL) and partitioned between EtOAc (100 mL) and H 2 O (50 mL).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…9 At the beginning, this ready dimerisation process complicated a direct synthesis of thiophene S-oxides by oxidation of thiophenes. In the mid-1990s four groups [11][12][13][14] almost simultaneously reported on the preparation and isolation of thiophene S-oxides by the oxidation of thiophenes with either organic peracids or with H 2 O 2 (Scheme 2) in the presence of either a Lewis acid (Scheme 3) or a proton acid. Although the steric effect of the substituents hindered dimerisation of the species, the yield of the thiophene Soxides at 5% was still low.…”
Section: Synthesismentioning
confidence: 99%